CSTUDI KASUS KINERJA PEGAWAI KECAMATAN CARINGIN DAN CIGOMBONG BERDASARKAN BUDAYA ORGANISASI DAN DISIPLIN KERJA PEGAWAI - Eddy Mulyadi Soepardi (Universitas Pakuan, 2015)
The purpose of this study is to determine the District Caringin Employee Performance analysis and Cigombong based on Cultural Organization and Work Discipline. The study population is all employees at Kecamatan Caringin by as many as 136 employees and employees of the District Cigombong by as many as 93 employees. The research instrument is a questionnaire. Collected data is processed using correlation analysis technique.The results show that: First, there is a positive relationship between organizational culture with employee performance with the power of a strong and significant correlation, with correlation coefficient (r) of 0.681, the coefficient of determination obtained by 46.4%, and a functional relationship equation Y = 26.923 + 0,747X1, meaning that there is a strong correlation between organizational culture with employee performance. So for that, if the organization has a good organizational culture automatically employee performance was good. Secondly, there is a positive relationship between the discipline of working with employee performance and the strength of the strong relationship that is equal to 0.645. Then the coefficient of determination of 41.6%. %. Functional relationship between the performance of employees working Discipline of Y = 36.505 + 0.692 X2. This means that the employee's performance is largely determined by the work discipline. Good working discipline will result in height the performance of employees at work and vice versa if the poor work discipline, the performance of lower-level officials. Secondly, there is a positive relationship between the discipline of working with employee performance and the strength of the strong relationship that is equal to 0.645. Then the coefficient of determination of 41.6%. %. Functional relationship between the performance of employees working Discipline of Y = 36.505 + 0.692 X2. This means that the employee's performance is largely determined by the work discipline. Good working discipline will result in height the performance of employees at work and vice versa if the poor work discipline, the performance of lower-level officials.Keywords: Employee Performance, Organiza tional Culture and Work Discipline.